Tipe Perilaku Impulsive Buying, Etnografi Para Digital Natives - Zsasa Novinda; Emma Yunika Puspasari (Universitas Medan Area, 2023)
The existence of increasingly sophisticated digital technology has caused people's activities to experience changes in terms of consumption. Jayabaya's prediction